Concluding Remarks: The Magisterium of Pius XII in a Historical Perspective - Unterburger, Klaus (JoMaCC, 2024)
From the 19th century onwards, ‘teaching’ was increasingly seen as the core task of the popes; the pontificate of Pope Pius XII can be seen here as a preliminary climax of an increasing intensification of the papal teaching office, which also extended to more and more topics. It was a relatively small group of theologians from the Roman universities who determined not only the work of the Holy Office, but also the drafting of papal teaching documents. Professionalisation and a certain standardisation of papal teaching were guided by the attempt to restrict themselves to the area of principles of faith and morals. Anti-modernist tendencies remained dominant; the relationship to the succeeding pontificate and the Second Vatican Council with its divergent objectives thus remains an open question.